2022
DOI: 10.3389/fpls.2022.799213
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to NaCl Osmotic Stress in Sequentially Harvested Hydroponic Red and Green Basil and the Role of Calcium

Abstract: Basil (Ocimum basilicum L.) is a heterogeneous reservoir of bioactive compounds that provide recognized benefits to human health, rendering it a model aromatic herb. Notwithstanding the application of nutritional stress, such as sodium chloride (NaCl) salinity, which mainly affects the primary metabolism, it also triggers adaptive mechanisms that involve the production of bioactive secondary metabolites. Genotype selection and the exogenous application of calcium chloride (CaCl2) help minimize salinity’s suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
(112 reference statements)
2
7
1
Order By: Relevance
“…However, it should be noted that ‘Anise’ and ‘Cinnamon’ did not differ significantly in height, number of leaves, and leaf area, although the total fresh weight was different ( Figure 3 A–C). Relative to total fresh weight, the significant differences observed between cultivars did not result in a different response to salt stress, unlike what Ciriello et al [ 27 ] observed in a recent work on basil. On average, salt treatment reduced the total fresh yield by 51.54% compared to the control; similar results were reported on Salvia officinalis L. [ 28 ] and Mentha spicata L. [ 29 ].…”
Section: Discussioncontrasting
confidence: 72%
“…However, it should be noted that ‘Anise’ and ‘Cinnamon’ did not differ significantly in height, number of leaves, and leaf area, although the total fresh weight was different ( Figure 3 A–C). Relative to total fresh weight, the significant differences observed between cultivars did not result in a different response to salt stress, unlike what Ciriello et al [ 27 ] observed in a recent work on basil. On average, salt treatment reduced the total fresh yield by 51.54% compared to the control; similar results were reported on Salvia officinalis L. [ 28 ] and Mentha spicata L. [ 29 ].…”
Section: Discussioncontrasting
confidence: 72%
“…On the other hand, the monovalent inorganic salt, NaCl, did not impair any of the agronomical parameters under low EC conditions. The importance of the osmotic potential on fresh and dry weight has been demonstrated by several studies, most of which focus on the osmotic stress induced by the presence of NaCl, probably due to its association with low irrigation water quality [ 52 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ], and few explore the effects of different salt sources such as KCl, Na 2 SO 4 , or CaCl 2 [ 86 , 87 , 88 , 89 ]. From these studies, the results of Ntatsi et al [ 86 ], who experimented on a salinity tolerant plant, Cichorium spinosum , also showed that under high salinity levels, CaCl 2 had a stronger effect on dry weight, even though under low salinity all the salts decreased both fresh and dry weight equally.…”
Section: Discussionmentioning
confidence: 99%
“…These thresholds refer to spinach, different types of lettuce, and rucola, and are set from approximately 2000 to a maximum of 5000 mg of NO 3 per kg of fresh weight, depending on the vegetable and season of reference. In the scope of protecting human health and keeping up with EU regulations, it has been suggested from several studies that the demonstrated antagonistic relations of nitrate and chloride can lead to a decreased nitrate content in leafy vegetables and, in several cases, this could be utilized for the production of “safer” foods [ 73 , 77 , 81 , 88 ]. Corn salad is considered a species with a high nitrate content (>2500 mg kg −1 of fresh weight) but its thresholds are not yet defined in the EU regulations [ 13 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quantification of the total phenol concentration of the leaves was determined according to the Folin–Ciocalteu method described by Ciriello et al [ 66 ]. 250 mg of freeze-dried and finely ground leaves were mixed with 10 mL of 60% methanol, shaken (15 min at 4000 rpm), and centrifuged.…”
Section: Methodsmentioning
confidence: 99%